Optimal taxation under regional inequality - Sebastian Kessing; Vilen Lipatov; J. Malte Zoubek (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2019)
Combining an intensive labor supply margin with an extensive, productivity-enhancing migration margin, we determine how regional inequality and labor mobility shape optimal redistribution. We propose the use of delayed optimal-control techniques to obtain optimal tax formulae with location-dependent productivity and multidimensional heterogeneity. Productivity-enhancing interregional migration exerts a downward pressure on marginal tax rates. Allowing for regionally differentiated taxation with location-dependent productivity, we find that marginal tax rates in high-(low-)productivity regions should be corrected downwards (upwards). Simula- tions using the productivity differences between metropolitan and other regions in the US indicate that productivity-increasing internal migration constitutes only a minor constraint on regionally undifferentiated redistributive taxation, but it is quantitatively more important for differentiated taxation.
Keywords: H11; J45; R12; 330; optimal taxation; redistribution; regional inequality; migration; multidimensional screening; delayed optimal control